PENGARUH PENERAPAN STRATEGI BELAJAR AKTIF TIPE STUDENT RECAP DISERTAI PETA KONSEP TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VIII SMPN 3 RANAH PESISIR - Oktafirda, Noci - (Pendidikan Biologi, 2014)
This research is background by low result of learning. This is caused because in learning process the students use note and teacherâs explanation, so there is no students activity and participation in teaching learning process, the students think biology is boring because just remember materials, and limit variation of strategy that is used in teaching and learning process, in teaching and learning process the teacher usually uses method because it is easer in implementing. One of alternative to solve the problem is implementing active learning strategy type student recap by using concept maps. This research has purpose to know the effect of implementing active learning strategy type Student Recap by using concept map toward result of students biology learning at class VIII in SMPN 3 Ranah Pesisir. Type of this research is experiment by using Randomized Control-Group Postes Only Design. Population of this research is students at class VIII in SMPN 3 Ranah Pesisir of academic year 2014/2015 that consist of five classes. Sample is taken by using purposive sampling. Technique of data analysis uses uji-T with corelation level of 95% (Î±= 0,05). The result of research shows that t-test 3,75 and t-table 1,68. t-test > t-table, it means that hypothesis (H1) is accepted. Based on data analysis shows that students behaviour and skill at class experiment more good that control class. From this research can be concluded that any effect of implementing active learning strategy type Student Recap by using concept map toward result of students biology learning at class VIII in SMPN 3 Ranah Pesisir.